Airflow dynamics in an emergency department: A CFD simulation study to analyse COVID-19 dispersion - Odi Fawwaz Alrebi (19499188) (2021)
Emergency departments (EDs) in hospitals are hotspots for highly transmissible infectious diseases and pose the most significant risk of viral infection spreading. With the recent COVID-19 outbreak, it became clear that emergency department design must evolve in order to be adequately prepared to handle the epidemic. The purpose of this research is to examine the design of the emergency department at a university hospital using a computational fluid dynamics (CFD) simulation based on the ANSYS CFX package. Turbulence Kinetic Energy and Velocity profiles were analyzed to determine which areas of the ED were most susceptible to virus spread. The analysis revealed that three critical areas of the emergency department, namely overnight patient beds, operating rooms, and resuscitation rooms, had significantly higher air velocity, dispersion, and mixing levels than the rest of the department's spaces. According to the two scenarios examined, the possibility of air transmission from these locations to neighboring areas becomes apparent, increasing the likelihood of transmitting the virus from these locations and infecting people in the adjacent areas, including patients and health care providers. Using the results of CFD simulations, a solution in the form of instructions for the arrangement of inlets and outlets, the separation of spaces, and the interior design of the spaces and hallways can be presented to the hospital administration. All of which can be implemented in the current design of the emergency department. Other Information Published in: Alexandria Engineering Journal License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.aej.2021.08.062